Metals and the Biology and Virulence of Brucella - Roop II, R. Martin; Caswell, Clayton C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book summarises the current knowledge on the role played by biologically relevant transition metals (Fe, Mn, Zn, Ni, Co, Cu and Mg) in the basic biology and virulence of bacterial pathogens from the genus Brucella. The authors explore the biological functions of these metals, how these bacteria compete with their mammalian hosts for these metals and how they avoid metal toxicity. Researchers and professionals studying zoonotic pathogens from the genus Brucella find this book valuable.
Metal requirements of Brucella strains -- Overcoming mammalian metal deprivation 'defenses' -. Fe, Mn, Zn -- Metal intoxication as a host defense -- Fe3+ import -- Mn dependent enzymes of  note -- Zn import by ZnuABC -- Ni import by NikABCDE -- Ni-, Cu- and Co-dependent enzymes of note.
Keywords: Organometallic chemistry .; Bacteria; Medical microbiology; Organometallic Chemistry; Bacteria; Medical Microbiology